A retrospective analysis of specialty match rate and gender trends in Canadian residency applications (2019–2024) - Lucy Hui; Katherine Feng; Jody Tao; Oswin Chang (PLoS ONE, 2025)
Background This study examines Canadian medical graduate (CMG) match outcomes from 2019 to 2024, focusing on applicant numbers, gender distribution, and match success. Methods A retrospective analysis was conducted using publicly available data from the CaRMS match reports. Specialty-specific application numbers and first-choice match rates were extracted. Match rates were calculated as the number of matriculates divided by the number of applicants, while competitiveness was determined by the number of first-choice applications per available position. Specialties were categorized into clinical, surgical, and diagnostic disciplines for trend analysis. Results From 2019 to 2024, CMG applicants decreased slightly from 5380 to 5346, while the total quota increased from 2800 to 2918. Family medicine saw a significant decrease in applications (r² = −0.849, p = 0.03), while anesthesiology had a significant increase (r² = 0.950, p < 0.01). Diagnostic disciplines like neuropathology decreased significantly (r² = −0.887, p = 0.02), while diagnostic radiology increased (r² = 0.842, p = 0.03). Surgical disciplines, including plastic surgery, had steady increases, with vascular surgery doubling its applications by 2023. Female applicants increased in clinical and surgical specialties but decreased in diagnostics. Match rates improved in family medicine (r2 = 0.964, p < 0.01), medical genetics (r2 = 0.817, p = 0.04), psychiatry (r2 = 0.839, p = 0.04), public health (r2 = 0.939, p < 0.01), and diagnostic and clinical pathology (r2 = 0.850, p = 0.03), while diagnostic radiology (r2 = −0.825, p = 0.04) declined. Female applicants had higher match rates in ophthalmology and pediatric neurology, while males led in orthopedic surgery. Conclusion Shifts in Canadian residency match trends from 2019 to 2024 may reflect the impact of the COVID-19 pandemic and evolving societal priorities. Ongoing monitoring of these trends is essential to ensure alignment with healthcare needs.